Potential economic benefits of restoring commercial oyster harvest levels in Apalachicola Bay, Florida - Robert Botta; Ed Camp; Christa Court; Caleb Stair; Charles Adams (EDIS)
Florida’s Apalachicola Bay has long been known for its oyster harvesting and processing industry, but a steady decline in oyster landings in the Bay has threatened the industry. The complex nature of the human and natural systems that together affect Apalachicola’s oyster reefs has created uncertainty about the long-term sustainability of the oyster fishing industry in Franklin County, which has prompted many questions about the ecology of the Bay and the economy of the region from a variety of stakeholders that directly or indirectly depend on the survival and successful restoration of the Apalachicola Bay oyster fishery. This 5-page fact sheet estimates the potential economic impacts associated with a successfully restored oyster reef in Apalachicola Bay, basing estimates on different hypothetical oyster harvest goals. Written by Robert Botta, Ed Camp, Christa Court, Caleb Stair, and Charles Adams and published by the UF/IFAS Food and Resource Economics Department, it is designed to inform decision making and discussions related to restoration and resource management in the region. https://edis.ifas.ufl.edu/fe1085